Excess adenosine A2B receptor signaling contributes to priapism through HIF‐1α mediated reduction of PDE5 gene expression. Issue 6 (10th March 2014) - Ning, Chen; Wen, Jiaming; Zhang, Yujin; Dai, Yingbo; Wang, Wei; Zhang, Weiru; Qi, Lin; Grenz, Almut; Eltzschig, Holger K.; Blackburn, Michael R.; Kellems, Rodney E.; Xia, Yang
ABSTRACT: Priapism is featured with prolonged and painful penile erection and is prevalent among males with sickle cell disease (SCD). The disorder is a dangerous urological and hematological emergency since it is associated with ischemic tissue damage and erectile disability. Here we report that phosphodiesterase‐5 (PDE5) gene expression and PDE activity is significantly reduced in penile tissues of two independent priapic models: SCD mice and adenosine deaminase (ADA)‐deficient mice. Moreover, using ADA enzyme therapy to reduce adenosine or a specific antagonist to block A2B adenosine receptor (ADORA2B) signaling, we successfully attenuated priapism in both ADA –/– and SCD mice by restoring penile PDE5 gene expression to normal levels. This finding led us to further discover that excess adenosine signaling via ADORA2B activation directly reduces PDE5 gene expression in a hypoxia‐inducible factor‐1α (HIF‐1α)‐dependent manner. Overall, we reveal that excess adenosine‐mediated ADORA2B signaling underlies reduced penile PDE activity by decreasing PDE5 gene expression in a HIF‐1α‐dependent manner and provide new insight for the pathogenesis of priapism and novel therapies for the disease.—Ning, C., Wen, J., Zhang, Y., Dai, Y., Wang, W., Zhang, W., Qi, L., Grenz, A ., Eltzschig, H. K., Blackburn, M. R., Kellems, R. E., Xia, Y. Excess adenosine A2B receptor signaling contributes to priapism through HIF‐1α mediated reduction of PDE5 gene expression. FASEB J . 28, 2725–2735 (2014). www.fasebj.org